Coronary tortuosity in patients with acetylcholine-induced coronary microvascular spasm. (3rd October 2022) - McChord, J; Gollwitzer, R; Seitz, A; Sechtem, U; Bekeredjian, R; Ong, P
Abstract: Background: Angina pectoris in the absence of relevant epicardial stenoses (ANOCA) is frequently caused by coronary microvascular spasm. It has been speculated that the morphology of epicardial coronary arteries is associated with microvascular spasm. One hypothesis is that the vasoconstriction of microvessels leads to intraluminal pressure increase in the vascular segments proximal to the spasm, which may shift the balance of vessel forces toward vessel elongation resulting in coronary tortuosity. Purpose: We assessed the relationship between epicardial coronary tortuosity and coronary spasm to elucidate a potential relationship between structural and functional coronary abnormalities. Methods: 610 patients (39% male, mean age 61 years) with stable angina yet unobstructed coronary arteries (<50% stenosis) were included in this study. All patients underwent invasive diagnostic coronary angiography followed by intracoronary acetylcholine (ACh) testing according to a standardized protocol. The ACh test was considered "positive" in the presence of (a) angina, ischemic ECG shifts during the test and ≥90% coronary diameter reduction ("epicardial spasm") or (b) all above without epicardial spasm ("microvascular spasm"). Assessment of coronary tortuosity was performed using left and right coronary images in multiple projections in a blinded fashion. The number and angles of the coronary curves in late diastole determined the severity of coronary tortuosity previously defined by Eleid. Patients were divided into those with at least moderate tortuosity versus those with no or mild tortuosity. Results: ACh-testing revealed epicardial spasm in 179 (29%) and microvascular spasm in 172 (28%) patients. The ACh-test was negative/inconclusive in the remaining 259 patients (43%). There were 298 patients (49%) with at least moderate coronary tortuosity. The remaining 312 patients had no or mild coronary tortuosity (51%). Patients with at least moderate tortuosity were more likely to have microvascular spasm (99 patients of 172 with microvascular spasm had at least moderate coronary tortuosity (58%) vs. 76 patients of 179 with epicardial spasm (43%) vs. 126 patients of 259 with negative/inconclusive ACh test (49%), p=0.017). Analysis of coronary tortuosity in patients with positive ACh-test showed that patients with at least moderate coronary tortuosity (n=175) had significantly more microvascular spasm (57%) than epicardial spasm (43%) (p=0.005). We also found that at least moderate coronary tortuosity was significantly more often found in patients with hypertension compared to patients without hypertension (230/438 vs. 71/172, p=0.015). Conclusions: In this large cohort of ANOCA patients coronary tortuosity was associated with hypertension and microvascular spasm. Our results provide interesting insights into the relationship of coronary morphology and vasomotor function. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Berthold-Leibinger-Foundation, Ditzingen, Germany